OCCUPATIONAL STRESS AMONG INTENSIVE CARE UNIT NURSES AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of occupational stress among nurses working in the Intensive Care Unit (ICU) using the Expanded Nursing Stress Scale (ENSS) at Viet Duc University Hospital in 2024.Methods: A cross-sectional study was conducted among 130 ICU nurses.Results: The mean ENSS score was 108.81 ± 28.51. The average age of participants was 34.38 ± 6.44 years, and the majority were female nurses (66.2%). The most stressful domains were related to: patient and family-related issues; confronting patient death; inadequate emotional preparation; and conflicts with physicians. Nurses aged ≤30 years reported significantly higher levels of occupational stress compared with those older than 30 years.Conclusion: The findings highlight an urgent need for greater attention to the psychological and mental well-being of healthcare workers.
Keywords: Nursing, Stress, Intensive Care Unit.